Study on Approaches for Reducing the Vibration Exposure of Hand-Helded Golf Club Heads Grinding - Bin Xiao; Yongjian Jiang; Wei Wen; Jianyu Guo; Maosheng Yan; Hansheng Lin; Shijie Hu (Proceedings, 2023)
To control vibration-induced white finger among workers performing the fine grinding of golf club heads, in this study, the influence of different factors on vibration acceleration were verified by adjusting the eccentric mass of different dynamic balance wheels, adjusting the angle of driving wheels and passive wheels, increasing the number of rubber cushions, and using new and old sand belts. This study determined that the eccentric mass of the dynamic balance wheel, the number of rubber pads, and the newness of the sand belt are significant factors affecting the vibration of workers. The vibration hazard posed to workers can be reduced by correcting the dynamic balance of the front wheel, increasing the amount of rubber pads, and replacing the type of sand belt with a newer one.